Analisis Kualitas Air Laut di Sekitar Jetty Penimbunan Bahan Bakar Minyak - Hildayani Hildayani; Andi Imran Anshari; Muhammad Nadir (Universitas Mataram, 2026)
Coastal areas are dynamic ecosystems that hold strategic value both ecologically and economically. The presence of infrastructure, such as jetties, has the potential to cause a decline in seawater quality in coastal regions. This study aims to determine the seawater quality and the Pollution Index based on physical, chemical, and microbiological parameters over a two-year period around a jetty used for fuel termina operations. The research was conducted in the sea water of Ulakan Village, Manggis District, Bali Province. The research method involved in-situ measurements of several parameters and the collection of seawater samples for laboratory analysis. The laboratory test results were then used to determine the seawater quality status using the Pollution Index (PI), based on the quality standards for marine life. The results showed that the seawater quality around the jetty for fuel storage operations exhibited significant dynamics in physical, chemical, and microbiological parameters throughout the period from 2024 to early 2025. Parameters that did not meet the established quality standards were water clarity in July 2024, as well as Copper (Cu) at locations AL2 and AL3 in January 2025. The Pollution Index analysis concluded that while all locations were initially in 'Good' condition in January 2024 with a value of 0.62, a degradation in quality occurred, moving into the 'Slightly Polluted' category in July 2024 with values ranging from 1.02 to 1.03. By January 2025, only location AL1 showed recovery in quality with an index of 0.59, demonstrating a better environmental recovery capacity in that area. Meanwhile, AL2 and AL3 experienced an increase in the index to 2.15 and 1.98, respectively, remaining in the 'Slightly Polluted' category.